Beneficial impact of indocyanine green fluorescence imaging on lymphadenectomy in laparoscopic total gastrectomy for advanced upper gastric cancer - Lv, Chen-Bin; Tong, Lin-Yan; Sun, Yu-Qin; Huang, Rong-Jie; Han, Huang-Huang; Chen, Qiu-Xian; Cai, Li-sheng (Frontiers in Oncology, 2025)
ObjectiveThis study aims to analyze the benefits of indocyanine green (ICG) fluorescence imaging on the efficacy of lymph node dissection (LND) during laparoscopic total gastrectomy (LTG) for advanced upper gastric cancer.Materials and methodsWe retrospectively analyzed the clinicopathological data of 98 patients with advanced upper gastric cancer undergoing LTG, including 29 patients in the ICG-guided group and 69 in the conventional LTG (non-ICG) group. The perioperative outcomes, efficiency of LND, and survival outcomes were compared between the two groups.ResultsThe mean number of lymph nodes (LNs) dissected was greater in the ICG group than the non-ICG group (52.34 vs. 37.38; P < 0.001). Additionally, the ICG group had more patients with > 30 dissected LNs (96.55% vs. 76.81%; P = 0.018). Notably, the ICG group exhibited a higher number of LNs dissected at stations 7, 8, 9, and 11 than the non-ICG group (P < 0.05). Metastatic LNs were more frequently identified among fluorescence-positive LNs (P = 0.002). ICG fluorescence imaging demonstrated excellent diagnostic performance for metastatic LNs with a sensitivity of 85.9% and a negative predictive value of 96%. The ICG and non-ICG groups showed comparable 2-year overall survival (86.2% vs 82.6%, p=0.737) and disease-free survival (82.8% vs 72.5%, p=0.203) rates.ConclusionsICG fluorescence imaging significantly improved lymphadenectomy precision during LTG for advanced upper gastric cancer, particularly in suprapancreatic nodal stations, and enhanced detection of metastatic LNs. However, no obvious survival benefit was observed within the limited follow-up period. Future prospective, multicenter studies are warranted to validate these results.